Considering Trade Policies for Liquid Biofuels - Kojima, Masami; Mitchell, Donald; Ward, William (World Bank, Washington, DC, 2014)
This report addresses the issues associated with trade in liquid biofuels is a second Energy Sector Management Assistance Program report on biofuels, and part of a broader assessment of bioenergy undertaken by the World Bank. The report asks how liberalizing trade in liquid biofuels might affect biofuel production and consumption. Bioenergy is playing an increasingly important role as an alternative and renewable source of energy. Bioenergy includes solid biomass, biogas, and liquid biofuels. Combustion of biomass residues for heat and power generation is commercially viable without government support in some applications. Liquid biofuels made from biomass are attracting growing interest worldwide, driven by concerns about energy security, climate change, and local environmental considerations and a desire to support domestic agriculture. The global liquid biofuel market today utilizes so called first generation technologies and relies mainly on agricultural food or feed crops for feedstock. Second generation biofuels, still far from commercially viable, can open up many new opportunities because they can be sourced from a much wider variety of feedstock's, vastly expanding the potential for fuel production and for abating greenhouse gas emission. The timing of commercialization is uncertain, although some industry analysts indicate that the needed cost reductions may be achieved in the coming decade. Focusing primarily on ethanol and biodiesel, the report takes a time horizon of the next 5 to 10 years. It outlines the important link between agriculture and biofuels, reviews past and present government policies for agriculture and for biofuels, and considers how these policies might affect the world biofuel market. The report highlights the links between the markets for oil, biofuels, feedstock's, and the by-products of biofuel processing. It reviews existing studies, examining the likely consequences of much larger biofuel production and trade liberalization of biofuels and their feedstock's. It concludes with policy considerations.